Relative energy production determines effect of repowering on wildlife mortality at wind energy facilities. Issue 6 (31st March 2021) - Huso, Manuela; Conkling, Tara; Dalthorp, Daniel; Davis, Melanie; Smith, Heath; Fesnock, Amy; Katzner, Todd
Abstract: Reduction in wildlife mortality is often cited as a potential advantage to repowering wind facilities, that is, replacing smaller, lower capacity, closely spaced turbines, with larger, higher capacity ones, more widely spaced. Wildlife mortality rates, however, are affected by more than just size and spacing of turbines, varying with turbine operation, seasonal and daily weather and habitat, all of which can confound our ability to accurately measure the effect of repowering on wildlife mortality rates. We investigated the effect of repowering on wildlife mortality rates in a study conducted near Palm Springs, CA. We controlled for confounding effects of weather and habitat by measuring turbine‐caused wildlife mortality rates over a range of turbine sizes and spacing, all within the same time period, habitat and local weather conditions. We controlled for differences in turbine operation by standardizing mortality rate per unit energy produced. We found that avian and bat mortality rate was constant per unit of energy produced, across all sizes and spacings of turbines. Synthesis and applications . In the context of repowering a wind facility, our results suggest that the relative amount of energy produced, rather than simply the size, spacing or nameplate capacity of the replacement turbines, determines the relative rate of mortality prior to and after repowering. Consequently, in a given location, newer turbines would be expected to be less harmful to wildlife only if they produced less energy than the older models they replace. The implications are far‐reaching as 18% of US and 8% of world‐wide wind power capacity will likely be considered for repowering within ~5 years. Abstract : In the context of repowering a wind facility, our results suggest that the relative amount of energy produced, rather than simply the size, spacing or nameplate capacity of the replacement turbines, determines the relative rate of mortality prior to and after repowering. Consequently, in a given location, newer turbines would be expected to be less harmful to wildlife only if they produced less energy than the older models they replace. The implications are far‐reaching as 18% of US and 8% of world‐wide wind power capacity will likely be considered for repowering within ~5 years. Resumen: La reducción en la mortalidad de fauna silvestre es citada a menudo como un posible beneficio de aumentar la potencia de las instalaciones de energía eólica. Estos cambios consisten en reemplazar turbinas pequeñas, de poca capacidad y alta densidad por turbinas de mayor tamaño, potencia y separación. Sin embargo, la tasa de mortalidad de la fauna no solo es afectada par el tamaño y separación de las turbinas, sino también por la forma de operar la turbina, estación, clima diario y hábitat. Todos estos factores pueden confundir nuestra capacidad para aislar el efecto del aumento de potencia. En este estudio, investigamos el efecto del aumento de potencia en la mortalidad de la fauna en una instalación en Palm Springs, CA. Controlamos por el efecto del clima y hábitat midiendo la mortalidad causada por turbinas de distinto tamaño y espaciamiento siempre durante el mismo periodo de tiempo, hábitat, y condiciones climáticas. Controlamos por diferencias en la operación de las turbinas estandardizando la mortalidad por unidad de energía producida. La mortalidad de aves y murciélagos por unidad de energía producida fue constante para todos los tamaños y espaciamientos de las turbinas. Síntesis y aplicación . Cuando se considera reemplazar una instalación eólica para aumentar su potencia, nuestros resultados sugieren que la cantidad relativa de energía producida, pero no el tamaño, espaciamiento o capacidad nominal de las nuevas turbinas, determina las tasas de mortalidad de la nueva instalación. Por lo tanto, en una instalación determinada, es de esperar que el impacto de las nuevas turbinas será menor solo si producen menos energía que los modelos que reemplazan. Las implicaciones de este estudio son importantes, dado que el 18% de la capacidad de energía eólica en los EEUU, y el 8% en el mundo, puede ser reemplazada por instalaciones de mayor potencia en los próximos 5 años.